Strengthening Ethical Codes to Prevent Discretion Misuse and Preserve Public Trust in Law Enforcement Practices - Dicki Agri Kurniawan; Megawati Barthos (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
This study examines the role of discretion exercised by law enforcement officers, especially within the context of criminal investigations. Discretion refers to the authority granted to investigators, prosecutors, and judges to make decisions that are not always explicitly regulated by written laws or regulations. It is granted to allow flexibility in addressing situations that require quick, context-specific decisions. Discretion is necessary because not every legal situation can be anticipated in advance by the law, especially in dynamic and unpredictable situations that law enforcement professionals encounter daily. However, the exercise of discretion must be grounded in the core principles of justice, legal certainty, and respect for human rights, ensuring that decisions are made fairly and in accordance with legal norms. While discretion allows law enforcement officers to exercise judgment and adapt to diverse situations, it also carries significant risks, particularly the potential for abuse of power. Such abuse could manifest in inappropriate criminalization of innocent individuals, discriminatory practices, or biased decisions that undermine the legitimacy of the justice system. The possibility of such negative consequences necessitates a careful and responsible approach to the application of discretion. Law enforcement officers must not only act in accordance with the law but also adhere to ethical standards and ensure that their decisions are made transparently and equitably. Therefore, the study emphasizes the need for strict oversight and the development of clear, consistent guidelines to govern the exercise of discretion. Supervision mechanisms, such as internal audits and external oversight bodies, are crucial in monitoring law enforcement activities and ensuring that officers do not misuse their powers. Furthermore, providing adequate training to law enforcement personnel on the ethical and legal boundaries of discretion is vital in preventing arbitrary or unjust decisions.